Revisiting Energy-Growth Hypothesis for Portugal Economy: A Case of Non-Linear ARDL in Production Function Framework (Journal of Asian Development Studies, 2025)
The role of energy consumption is crucial in determining economic growth of any economy. Its impact is different in different economies. Therefore, in the present study we have attempted to investigate the non-linear impact of energy consumption by taking natural resource rent and trade openness as control factors in a production function framework for Portugal economy to see whether energy consumption accelerate economic growth in the pre-production stages or it hampers it. Similarly, we are also interested to see how energy consumption influences economic growth in the mature-stages of production. In order to find the answer for our question, we will utilize ARDL approach by taking data series from 1980 to 2022. The estimated results reveal that energy consumption significantly expands economic growth in the pre-production stages while it hampers economic growth in the mature-production stages. This confirms the inverted U-shaped impact of energy consumption on economic growth. The results further show that capital formation, trade openness and natural resource rent significantly stimulate economic growth in Portugal. This concludes that natural resource rents are blessing for Portugal economy and trade led growth hypothesis is also valid for Portugal.